2019
DOI: 10.1590/2317-1545v41n3212746
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging test and its relationship to physiological potential of soybean seeds

Abstract: Although accelerated aging is one of the tests most used for evaluation of the physiological quality of soybean seeds, there are few studies that relate it to other physiological tests used for the crop. In this context, the objective of this study was to investigate the relationship of accelerated aging to the results of physiological performance obtained in the vigor tests most frequently used in the soybean quality control system (germination, first count, seedling vigor classification, accelerated aging, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…Comparison of the variables evaluated shows that the equations are fitted in a satisfactory manner because the results estimated generally have the same tendency as the results obtained. Matera et al (2019) worked with soybeans seeds and also found accuracy among the variables evaluated -most prominently for the electrical conductivity and percentage of seedling emergence in the field tests, with accelerated aging as the dependent variable. Table 5 also shows that the lowest values of leaching Table 5.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Comparison of the variables evaluated shows that the equations are fitted in a satisfactory manner because the results estimated generally have the same tendency as the results obtained. Matera et al (2019) worked with soybeans seeds and also found accuracy among the variables evaluated -most prominently for the electrical conductivity and percentage of seedling emergence in the field tests, with accelerated aging as the dependent variable. Table 5 also shows that the lowest values of leaching Table 5.…”
Section: Resultsmentioning
confidence: 91%
“…The results of the electrical conductivity test showed strong negative correlation with the tests of germination (r = -0.81), tetrazolium vigor (r = -0.84), accelerated aging (r = -0.86), first germination count (r = -0.78), seedling emergence in the field (r = -0.79) and seedling emergence in sand (r = -0.85) ( Table 3). Barros and Marcos-Filho (1997), Barbieri et al (2013), Schuab et al (2006) and Matera et al (2019) worked with soybean seeds and also found strong negative correlation between the electrical conductivity test and the tests of germination, accelerated aging and seedling emergence in the field. This is a strong indication that the test can and should be part of programs for quality control of soybean seeds, considering that such programs should always work with more than one procedure, thus assisting in decision making regarding the use of seed lots.…”
Section: Resultsmentioning
confidence: 96%
“…An analysis of the effect of localities and climatic conditions on seed quality and viability in different soybean genotypes was conducted by Vujaković et al (2011a), who showed that the quality and vigour of seeds were influenced by genotype and agro-ecological conditions in soybean seed production. The accelerated ageing test can be used to obtain data on the physiological quality of seeds, predict germination in the field, and assess seedling vigour, or as an aid in the interpretation of soybean seed lot vigour (Matera et al, 2019).…”
Section: Accelerated Ageing Testmentioning
confidence: 99%
“…A database containing information and visual characteristics of soybean seeds classified according to the types and intensity of damage obtained by the tetrazolium test was published by Pereira et al (2019). The set of these data enables an efficient way of automatic definition of soybean seed vigour through machine learning and data collection methods, which can be useful for researchers, seed analysts and farmers.…”
Section: Tetrazolium Testmentioning
confidence: 99%
“…For this it is necessary to carry out vigor analysis tests and currently, there are numerous methodologies. However, it is known that the accelerated aging test is one of the most used for soybean crops, as it provides a high level of stress to the seeds, with high temperature and high humidity (MATERA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%